Identification of Damaging nsSNVs in HumanERCC2 Gene. (24th May 2016) - Fang, Shuo; Zhang, Yuntong; Xu, Miao; Xue, Chunyu; He, Lin; Cai, Lei; Xing, Xin
Abstract : The hERCC2 gene is an important DNA repair molecule for initiating Cutaneous melanoma (CM). Therefore, it is advisable to study the possible functional SNVs in hERCC2 . To achieve this goal, we collected total 2, 253 SNVs in hERCC2 from the EMBL website, of which 303 are non‐synonymous single nucleotide variants (nsSNVs). Then, SIFT and PolyPhen were used to predict the damaging nsSNVs, and four nsSNVs (rs368866996, rs377739017, rs370819591, and rs121913022) were suggested to be damaging mutations. Since I‐Mutant2.0 showed a decrease in stability for the mutants containing each of the four nsSNVs, a 3D protein structure was modeled. Based on the comparison of the energy after minimization, RMSD and stabilizing residues between the native and mutant proteins' structure, rs121913022 was proposed to be the most damaging variant among the nsSNVs in hERCC2 gene by decreasing the stability of protein. The mutant G713R of hERCC2 protein caused by rs121913022 was found to have less expression level than native hERCC2 protein in melanoma cells. These results suggest that rs121913022 may have potentially important clinical and drug target implications. Abstract : Cutaneous melanoma is a malignant cancer involved with ERCC2 gene. The roles of comprehensive nsSNP in ERCC2 have been studied. Based on the comparison of 3D structure information between the native and mutant proteins, the mutant G713R of ERCC2 protein caused by the rs121913022 is proposed to be the most damaging variant and validated to have less expression level than native ERCC2 in melanoma cells.